Powder, negative electrode active material for metal-air battery, reaction agent for hydrogen production device, and method for producing powder
Patent Information
- Application Number
- CN202580022020.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-04-22
- Filing Date
- 2025-03-13
- Publication Date
- 2026-10-27
AI Technical Summary
根据本发明,能够提供具有高的反应效率、并且即使反复进行氧化还原反应也能够维持反应效率的粉末。
Smart Images

Figure CN122996040A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to powders, negative electrode active materials for metal-air batteries, reactants for hydrogen production devices, and methods for manufacturing powders. Background Technology
[0002] Iron is an inexpensive and reliably supplied metal, therefore, hydrogen production devices and metal-air batteries utilizing the redox reaction of iron, as shown below, are under development. Here, M represents metallic iron, and MO represents iron oxide.
[0003] M + H₂O → MO + H₂ (hydrogen release, discharge) MO + H2 → M + H2O (hydrogen storage, charging) In order to improve the reaction efficiency of the above-mentioned redox reaction, iron powder is usually used as the aforementioned metallic iron in hydrogen production devices and metal-air batteries.
[0004] For hydrogen production devices and metal-air batteries, high operating temperatures are used to utilize the aforementioned redox reaction of iron. However, when the specific surface area of the iron powder is large, the iron particles constituting the iron powder sinter together due to the influence of temperature, and the iron particles become coarser. As a result, the specific surface area of the iron powder decreases, and therefore, the reaction efficiency of the redox reaction decreases significantly due to repeated use.
[0005] To address the aforementioned issues, methods are being investigated to prevent iron particles from sintering due to the heat of the redox reaction.
[0006] For example, Patent Document 1 discloses a negative electrode for an air battery obtained by coating particulate iron with an oxide of a chemically stable compound such as aluminum or zirconium at the operating temperature of an air battery.
[0007] Patent document 2 discloses a powder containing iron oxide particles, which is a powder made by adding sintering inhibitor to iron oxide, containing plate-shaped particles formed by the aggregation of iron oxide particles and sintering inhibitor.
[0008] Existing technical documents Patent documents Patent Document 1: Japanese Patent Application Publication No. 2015-216109 Patent Document 2: Japanese Patent Application Publication No. 2022-15292 Summary of the Invention
[0009] The problem that the invention aims to solve According to Patent Documents 1 and 2, it is claimed that an air battery can maintain reaction efficiency (excellent charge-discharge cycle characteristics) even when repeated redox reactions are carried out. However, Patent Documents 1 and 2 have the following problems.
[0010] First, even when using the negative electrode for air batteries disclosed in Patent Document 1, the oxidation rate is still prone to decrease due to the sintering of iron, requiring improved performance to maintain reaction efficiency during repeated redox reactions.
[0011] In addition, when iron-containing powder is used in metal-air batteries or hydrogen production devices, it is tightly packed in the battery cell, but the iron oxide-containing powder disclosed in Patent Document 2 cannot fully maintain the reaction efficiency of the redox reaction under such actual use conditions.
[0012] The present invention was made in view of the above circumstances, and the object is to provide a powder with high reaction efficiency and which can maintain reaction efficiency even when repeated redox reactions are carried out.
[0013] Methods for solving problems The inventors of this application conducted in-depth research and discovered that the above-mentioned objectives can be achieved by adopting the following configuration, thereby completing the present invention.
[0014] 1. A powder comprising: Iron oxide particles; and oxide particles, The aforementioned oxide particles contain at least one of Cr and Si in the form of oxides. The average particle size of the aforementioned oxide particles is between 0.5 nm and 100 nm. The maximum Freette diameter F of the aforementioned oxide particles max With the minimum Fret diameter F min The ratio of F max / F min The average value is above 2.0. The aforementioned oxide particles are in contact with the aforementioned iron oxide particles at an average contact rate of 20% to 80% relative to the aforementioned iron oxide particles.
[0015] 2. A negative electrode active material for a metal-air battery, which uses the powder described in 1 above.
[0016] 3. A reactant for a hydrogen production apparatus, which uses the powder described in 1 above.
[0017] 4. A method for manufacturing the powder described in 1 above, comprising: An adhesion process that attaches a compound containing at least one of Cr and Si to iron oxide powder; A heat treatment process that involves heat-treating the aforementioned adhered powder; and A reduction-oxidation process is performed on the heat-treated powder after reduction at a reduction temperature of 450°C or below, followed by oxidation of the reduced powder.
[0018] 5. The method for manufacturing the powder described in 4 above, wherein the aforementioned adhesion step is to... Iron oxide powder: 80% or more, and A mixing process involving powders containing oxides of at least one of Cr and Si: 3% or more of the powder is mixed.
[0019] The effects of the invention According to the present invention, a powder with high reaction efficiency can be provided, and the reaction efficiency can be maintained even when repeated redox reactions are carried out. Attached Figure Description
[0020] [ Figure 1 [This is a diagram used to illustrate the morphology of iron oxide particles and oxide particles.]
[0021] [ Figure 2 [This is a schematic diagram illustrating a metal-air battery according to an embodiment of the present invention.]
[0022] [ Figure 3 [This is a schematic diagram used to illustrate the battery cells used in the embodiments.] Detailed Implementation
[0023] The inventors of this application conducted in-depth research on powders with high reaction efficiency that can maintain reaction efficiency even during repeated redox reactions. As a result, it was discovered that it is effective to bring fine oxide particles containing at least one of Cr and Si in oxide form into contact with a portion of the surface of iron oxide particles, thus completing this invention.
[0024] The preferred embodiments of the present invention will be described below. It should be noted that the present invention is not limited to the following embodiments. Furthermore, in this specification, the numerical range indicated by "~" refers to the range including the values before and after "~" as both the lower and upper limits.
[0025] The powder involved in this invention comprises Iron oxide particles; and oxide particles, The aforementioned oxide particles contain at least one of Cr and Si in the form of oxides. The average particle size of the aforementioned oxide particles is between 0.5 nm and 100 nm. The maximum Freette diameter F of the aforementioned oxide particles max With the minimum Fret diameter F min The ratio of Fmax / F min The average value is above 2.0. The aforementioned oxide particles are in contact with the aforementioned iron oxide particles at an average contact rate of 20% to 80% relative to the aforementioned iron oxide particles.
[0026] [Iron oxide particles] The aforementioned iron oxide particles serve as the substrate for the aforementioned powder.
[0027] (Types of iron oxide) The type of iron oxide constituting the iron oxide particles is not limited; for example, it can be one or more components selected from the group consisting of Fe2O3 (hematite), Fe3O4 (magnetite), and FeO. However, Fe2O3 and Fe3O4 are stably formed in the oxidation reaction of iron, so from the viewpoint of ease of manufacture, the aforementioned iron oxide preferably contains one or both of Fe2O3 and Fe3O4. Furthermore, the ratio of Fe2O3 to Fe3O4 content in the aforementioned iron oxide particles is not particularly limited. That is, the aforementioned iron oxide particles may contain only Fe2O3 as iron oxide, or they may contain only Fe3O4 as iron oxide.
[0028] The aforementioned iron oxide particles may be formed from iron oxide, but may also contain unavoidable impurities in addition to the aforementioned iron oxide. Furthermore, the aforementioned iron oxide particles may contain trace amounts of added elements. Examples of added elements include, for example, C, Al, P, S, Cl, and Mn. The total content of the added elements may, for example, be less than 3% by mass. The aforementioned iron oxide particles may contain at least one selected from C, Al, P, S, Cl, and Mn in an amount less than 3% by mass, with the balance being O, Fe contained in the form of iron oxide, and unavoidable impurities.
[0029] (content) The content of the aforementioned iron oxide particles is not particularly limited. A higher content of iron oxide particles results in a greater amount of iron oxide participating in the redox reaction, thus increasing the amount of hydrogen and charge that can be recovered through the redox reaction, further improving the reaction efficiency when used in metal-air batteries or hydrogen production devices. Therefore, the content of the aforementioned iron oxide particles relative to the overall powder is preferably 80 mass% or more, more preferably 85 mass% or more, and even more preferably 90 mass% or more. The upper limit of the content of the aforementioned iron oxide particles relative to the overall powder is not particularly limited, but considering its relationship with oxide particles, it is preferably set to 97 mass% or less.
[0030] (Particle shape) The shape of the aforementioned iron oxide particles is not particularly limited. For example, they can be spherical, polyhedral, or plate-like. From the viewpoint of improving the filling rate of the cell in a metal-air battery, spherical or polyhedral shapes are preferred.
[0031] (Average particle size) The smaller the average particle size (primary particle size) of the aforementioned iron oxide particles, the larger the specific surface area and the higher the reaction rate. Therefore, the average particle size is preferably 1000 nm or less, more preferably 700 nm or less. On the other hand, if the average particle size is too small, the oxide becomes difficult to adhere, resulting in a decrease in reaction efficiency when used in metal-air batteries or hydrogen production devices. Therefore, the average particle size is preferably 10 nm or more, more preferably 50 nm or more. It should be noted that the particle size of the aforementioned iron oxide particles uses the equivalent circular diameter of the iron oxide particles. Furthermore, the average particle size of the iron oxide particles is measured using a scanning electron microscope (SEM). More specifically, it is measured using the method shown below.
[0032] First, the aforementioned powder was fixed onto conductive tape. To ensure conductivity, carbon was deposited by vapor deposition to prepare the test sample. The test sample was observed using SEM, and the equivalent circle diameter of the iron oxide particles was calculated through image processing.
[0033] [Oxide particles] The oxide particles function as sintering inhibitors for the aforementioned iron oxide particles. These oxide particles, in the form of oxides, contain at least one of Cr and Si, with an average particle size of 0.5 nm to 100 nm and a maximum Ferete diameter F. max With the minimum Fret diameter F min The ratio of F max / F min The average value is 2.0 or higher. Furthermore, the aforementioned oxide particles are in contact with the aforementioned iron oxide particles at an average contact rate of 20% to 80% relative to the aforementioned iron oxide particles.
[0034] (Element) The aforementioned oxide particles contain at least one of Cr and Si in the form of oxides. That is, the aforementioned oxide particles contain oxides having at least one of Cr and Si. Examples of oxides having at least one of Cr and Si include Cr₂O₃, (Fe,Cr)₂O₃, (Fe,Cr)₃O₄, Cr₂MnO₄, SiO₂, FeSiO₄, and MnSiO₃. The aforementioned oxide particles may contain a variety of oxides. The metal elements contained in the aforementioned oxide particles in the form of oxides are not limited to Cr and Si; for example, Fe, Mn, etc., may also be included. Furthermore, the aforementioned oxide particles may contain trace amounts of additive elements. However, in order to more effectively suppress sintering, the total proportion of Cr and Si in the aforementioned oxide particles in the form of oxides is preferably 25% or more in terms of atomic ratio. There is no upper limit to this proportion, and it can be 100%.
[0035] The aforementioned oxide particles are preferably formed from oxides containing at least one of Cr and Si. Furthermore, the aforementioned oxide particles may contain unavoidable impurities in addition to the oxides containing at least one of Cr and Si, and may also contain trace amounts of additives. Examples of additives include C, nitrides, and oxides without Cr and Si (e.g., oxides selected from at least one element selected from Al, Cl, Mn, and Fe). The total content of the additives may, for example, be less than 3% by mass. The aforementioned oxide particles may contain less than 3% by mass of additives in total content, with the balance being oxides containing at least one of Cr and Si and unavoidable impurities. Additionally, the total content of C, N, Al, Cl, Mn, and Fe may be less than 3% by mass.
[0036] (Average particle size) The average particle size of the aforementioned oxide particles was set to be 0.5 nm to 100 nm. When the average particle size is less than 0.5 nm, it is difficult to obtain a sufficient sintering inhibition effect, and the reaction efficiency decreases during repeated redox reactions. Therefore, the average particle size was set to be 0.5 nm or more. On the other hand, when the average particle size is greater than 100 nm, it hinders the reduction reaction of iron oxide particles and the oxidation reaction of the iron particles generated by this reduction reaction, making it impossible to produce a sufficient redox reaction commensurate with the amount of iron oxide particles. That is, the reaction efficiency decreases when used in metal-air batteries. Therefore, the average particle size was set to be 100 nm or less. It should be noted that the average particle size of the aforementioned oxide particles uses the equivalent circle diameter observed by SEM. Specifically, the average particle size was determined using the method described in the examples.
[0037] (F) max / F min (average) In this invention, the maximum Ferete diameter F of the aforementioned oxide particles is... max With the minimum Fret diameter F min The ratio is F max / F min Setting the average value above 2.0 is important. F max / F min When the average value is less than 2.0, the reaction efficiency deteriorates during repeated redox reactions. That is, if the adhesion between oxide particles and iron oxide particles is low, the contact between iron oxide particles and oxide particles becomes insufficient during repeated redox reactions, leading to reduced reaction efficiency. Therefore, to improve the aforementioned adhesion, it is necessary to control the shape of the oxide particles; specifically, it is necessary to control the shape of the F... max / F min The average value is set to 2.0 or higher. It should be noted that the adhesion between iron oxide and oxide particles can also be ensured by aggregating them into plate-like aggregates. However, if F is used... max / F min Oxide particles with an average value less than 2.0 are considered primary particles, and when they aggregate to form aggregates, the density of the molded body decreases as a large amount of these aggregates are included. In metal-air batteries or hydrogen production devices, if the iron-containing powder is not filled with sufficient density, the reaction efficiency during repeated redox reactions decreases. That is, even if the reaction efficiency can be maintained when the powder is used directly for evaluation, the same effect cannot be obtained when it is used in metal-air batteries or hydrogen production devices. Therefore, with regard to the powder of the present invention, by making F max / F min The average value is within the above range, thus preventing a decrease in reaction efficiency during repeated redox reactions in the actual use environment of metal-air batteries or hydrogen production devices. On the other hand, F max / F min There is no specific upper limit to the average value; for example, it can be below 5.0.
[0038] The maximum Freette diameter F of the aforementioned oxide particles max and minimum Freette diameter F min and F max / F min The average value was determined using SEM. Specifically, it was determined using the method described in the examples.
[0039] (Average contact rate) In order to achieve the effect of inhibiting sintering, it is important that the aforementioned oxide particles are in contact with the aforementioned iron oxide particles. Figure 1An example is shown of the morphology of the iron oxide particles and oxide particles contained in the powder involved in this invention. Figure 1 The oxide particles shown are present in contact with iron oxide particles. Here, the proportion of iron oxide particles in contact with the oxide particles relative to the outer periphery of the iron oxide particles is called the contact rate. In this invention, the average contact rate is set to be 20% or more and 80% or less. That is, the oxide particles are present in contact with the iron oxide particles at an average contact rate of 20% or more and 80% or less relative to the iron oxide particles. When the average contact rate is less than 20%, a sufficient sintering inhibition effect cannot be obtained. Therefore, the average contact rate is set to be 20% or more. In addition, when the average contact rate is greater than 80%, it hinders the reduction reaction of iron oxide particles and the oxidation reaction of iron particles generated by the reduction reaction, and a sufficient redox reaction corresponding to the amount of iron oxide particles cannot be generated. That is, the reaction efficiency is reduced when used in metal-air batteries. Therefore, the average contact rate is set to be 80% or less.
[0040] The aforementioned average contact rate was determined using scanning transmission electron microscopy (STEM) and energy dispersive X-ray spectroscopy (EDS). Specifically, it was determined using the methods described in the examples.
[0041] [powder] The powder involved in this invention can be formed from iron oxide particles and oxide particles. Furthermore, the powder may contain other substances besides iron oxide particles and oxide particles. These other substances can be any substance without particular limitation, as long as they do not hinder the redox reaction of the powder. For example, these other substances can be impurities introduced during the manufacture of the powder. Examples of such impurities include, for instance, the material of the grinding balls and jar of a ball mill; specifically, ZrO2, Al2O3, etc. The content of these other substances is preferably 17 mass% or less, more preferably 10 mass% or less, and even more preferably 5 mass% or less. There is no lower limit to the content of these other substances; it can be 0 mass.
[0042] The powder described in this embodiment can suppress the sintering of iron oxide particles during repeated redox reactions, thus maintaining reaction efficiency. Therefore, the powder described in this embodiment can be suitably used as a reactant in a hydrogen production device that extracts hydrogen generated in an oxidation reaction, and as a negative electrode active material in a metal-air battery.
[0043] [Negative electrode active material for metal-air batteries] One embodiment of the present invention relates to a negative electrode active material for a metal-air battery that uses the aforementioned powder. The aforementioned negative electrode active material can be formed from the aforementioned powder, or it may contain components other than the aforementioned powder. Furthermore, the aforementioned negative electrode active material may comprise powder obtained by reducing iron oxide contained in the aforementioned powder, or it may be formed from powder obtained by reducing iron oxide contained in the aforementioned powder.
[0044] use Figure 2 A metal-air battery (iron-air battery) using the negative electrode active material described in this embodiment will be explained. Figure 2 As shown, in the metal-air battery 5, an air electrode 2 is disposed on one side of the solid electrolyte 3, and the air electrode 2 is in contact with air. Furthermore, a negative electrode 4 is disposed on the opposite side, and a negative electrode active material 1 is disposed within a sealed space connected to the negative electrode 4.
[0045] During discharge, Figure 2 The reaction is indicated by the solid arrow. First, at air electrode 2, O2 combines with electrons to form O2. - Next, at the negative electrode active material 1, an oxidation reaction of iron occurs, producing hydrogen. This hydrogen reacts with O2. - Water is formed by the combination of electrons, which flow out from the negative electrode side. As a result, current flows from the air electrode 2 towards the negative electrode 4 via wiring (not shown).
[0046] During charging, such as Figure 2 As indicated by the dashed arrow, the reaction occurs in the opposite direction to that during discharge. First, at the negative electrode active material 1, a reduction reaction of iron occurs, producing water. The water produced is then decomposed into hydrogen and O2 by electrons flowing into the negative electrode 4. - The generated O2 - Electrons are released at air electrode 2 to become O2, which is then released to the outside. As a result, current flows from negative electrode 4 towards air electrode 2 via wiring (not shown).
[0047] Regarding metal-air batteries using the aforementioned negative electrode active material, it is preferable to set the operating temperature below 600°C. Furthermore, to ensure the redox reaction proceeds fully, it is preferable to set the operating temperature above 200°C.
[0048] [Reactants for hydrogen production units] One embodiment of the present invention relates to a hydrogen production apparatus using a reaction agent that utilizes the aforementioned powder. The aforementioned reaction agent may comprise a powder obtained by reducing iron oxide contained in the aforementioned powder, or it may be formed from the aforementioned powder. The reaction agent may also contain components other than the aforementioned powder.
[0049] In the hydrogen production apparatus using the reactant according to this embodiment, firstly, if the reactant contains iron oxide, the iron oxide can be reduced to produce metallic iron. Then, by contacting water vapor with the reduced reactant, hydrogen can be generated along with the oxidation of the metallic iron.
[0050] Regarding hydrogen production apparatuses using the aforementioned reactants, it is preferable to keep the temperature of the reactants below 600°C. Alternatively, it is preferable to keep the temperature of the reactants above 200°C.
[0051] [Manufacturing Method] The powder manufacturing method of the present invention comprises: an attachment step of attaching a compound containing at least one of Cr and Si to iron oxide powder; a heat treatment step of subjecting the attached powder to heat treatment; and a reduction oxidation step of subjecting the heat-treated powder to reduction and the reduced powder to oxidation.
[0052] (Iron oxide powder) There are no particular limitations on the iron oxide powder used; any type of iron oxide powder can be used. For example, iron oxide powder that can be obtained as an industrial material such as a pigment or ferrite raw material can be used. Alternatively, iron oxide powder produced by conventional methods such as wet or dry processes, using ferrous sulfate or ferrous chloride, can also be used. The type of iron oxide constituting the iron oxide powder is the same as that of the iron oxide particles mentioned above.
[0053] The average particle size of the aforementioned iron oxide powder is not particularly limited. However, in order to facilitate the adhesion of oxide particles to the surface of iron oxide particles, it is preferable that the average particle size of the aforementioned iron oxide powder is 50 nm or more. On the other hand, when the average particle size of the iron oxide powder is greater than 1000 nm, the specific surface area decreases and the redox rate decreases. Therefore, from the viewpoint of reaction rate, it is preferable that the average particle size of the iron oxide powder is 1000 nm or less.
[0054] (Attachment process) In the aforementioned adhesion step, a compound containing at least one of Cr and Si is adhered to the iron oxide powder. The method of adhesion is not limited. For example, it can be a method of mixing iron oxide powder with a powder containing an oxide of at least one of Cr and Si. That is, the aforementioned adhesion step can be a mixing step of mixing iron oxide powder and a powder containing an oxide of at least one of Cr and Si. In the aforementioned mixing step, the mixing ratio of iron oxide powder is set to 80 mass% or more, and the mixing ratio of the powder containing the oxide of at least one of Cr and Si is set to 3 mass% or more. Alternatively, in addition to the above method, a method of vacuum evaporating an oxide containing at least one of Cr and Si onto iron oxide powder, or a method of immersing iron oxide powder in a Cr-containing solution or a Si-containing solution, can also be used. In other words, the aforementioned adhesion step can be a vacuum evaporation step of vacuum evaporating an oxide containing at least one of Cr and Si onto iron oxide powder, or an immersion step of immersing iron oxide powder in a Cr-containing solution or a Si-containing solution.
[0055] <Mixed Process> When mixing iron oxide powder and oxide powder, in order to achieve an average contact rate of less than 80% for the final powder and to prevent the oxide particles from becoming coarse, the mixing ratio of the iron oxide powder is set to 80 mass% or more. Considering the relationship with the mixing ratio of the oxide powder described later, the upper limit of the mixing ratio of the iron oxide powder is set to 97 mass% or less.
[0056] Furthermore, the mixing ratio of the powder containing oxides of at least one of Cr and Si is set to 3 mass% or more. This allows the content of the aforementioned oxide particles in the final powder to be set to 3 mass% or more, thereby improving the aforementioned average contact rate. On the other hand, considering the relationship with the mixing ratio of iron oxide powder, the aforementioned mixing ratio is set to 20 mass% or less.
[0057] The oxide powder used is not particularly limited; for example, powders of Cr2O3, (Fe,Cr)2O3, (Fe,Cr)3O4, Cr2MnO4, SiO2, FeSiO4, MnSiO3, etc., can be used. The type of oxide constituting the oxide powder can be the same as that of the oxide particles described above. Furthermore, for example, oxide powders that can be obtained as reagents or those that can be obtained as industrial materials can be used. The average particle size of the oxide powder is not particularly limited and can be approximately several tens of nm to several μm.
[0058] The mixing method is not particularly limited, but mechanical mixing is preferred. A mixer such as a ball mill can be used as the mixing method. The operating conditions of the mixer are not limited. However, for example, when using a ball mill, by slowing down the rotation speed of the ball mill, it is possible to prevent the particles from becoming plate-shaped while allowing the oxide to adhere to the surface of the iron oxide particles, thereby improving the filling rate during the compression molding of the obtained powder. From this viewpoint, the rotation speed of the ball mill is preferably 400 rpm or less. Furthermore, the mixing time is preferably 1.0 hour or more.
[0059] The aforementioned mixing is preferably carried out in a solvent. There are no particular limitations on the solvent used; alcohols such as ethanol can be suitably used.
[0060] <Vacuum Evaporation Process> When using a method of vacuum evaporating an oxide containing at least one of Cr and Si onto iron oxide powder, the aforementioned iron oxide powder can be suitable as the iron oxide powder. Furthermore, the composition of the oxide containing at least one of Cr and Si can be set to be the same as the composition of the aforementioned oxide particles. In the case of vacuum evaporation, by controlling the evaporation time and the power input to the vacuum evaporation apparatus, the content of the aforementioned oxide and the content of iron oxide particles in the deposited powder can be kept within the aforementioned range. Additionally, the evaporation process can be performed multiple times. It should be noted that it is preferable to stir the obtained powder between each evaporation.
[0061] <Immersion Process> When using a method of impregnating iron oxide powder in a Cr-containing solution or a Si-containing solution, the aforementioned iron oxide powder can be used as the iron oxide powder. There are no particular limitations on the aforementioned Cr-containing solution or Si-containing solution; for example, a solution containing Cr nitric acid can be used.
[0062] (Heat treatment process) In the heat treatment process, the powder after the aforementioned adhesion process is subjected to heat treatment. By performing heat treatment, the adhesion between oxide particles and iron oxide particles can be improved.
[0063] In the aforementioned heat treatment process, the heat treatment temperature is not particularly limited, but by increasing the heat treatment temperature, the adhesion between the oxide particles and iron oxide particles in the final powder can be improved. Therefore, the aforementioned heat treatment temperature is preferably 600°C or higher. On the other hand, if the heat treatment temperature is too high, sintering of the iron oxide powder will occur. Therefore, from the viewpoint of further improving reaction efficiency, the aforementioned heat treatment temperature is preferably 1000°C or lower.
[0064] In the aforementioned heat treatment process, the holding time is not particularly limited. By extending the holding time, the adhesion between the oxide particles and iron oxide particles in the final powder can be improved. On the other hand, if the holding time is too long, sintering of the iron oxide powder may occur, resulting in insufficient reaction efficiency. Therefore, the holding time of the aforementioned heat treatment is preferably 30 seconds or more. Furthermore, the holding time of the aforementioned heat treatment is preferably 24 hours or less. More specifically, when the heat treatment temperature is 600°C, it is preferably 1 hour to 24 hours; when it is 800°C, it is preferably 1 minute to 30 minutes; and when it is 1000°C, it is preferably 30 seconds to 10 minutes.
[0065] (Reduction oxidation process) In the reduction oxidation process, the aforementioned heat-treated powder is reduced at a specified reduction temperature, thereby oxidizing the reduced powder. Through this reduction and oxidation, the oxide particles attached to the iron oxide particles shrink, thus cracking while maintaining their attached state, resulting in elongated oxide particles. Therefore, the desired average particle size, average contact ratio, and F0 can be achieved. max / F min The average value.
[0066] In the aforementioned reduction-oxidation process, if the reduction temperature is too high, the oxide particles will change from elongated to nearly spherical, making it impossible to achieve the aforementioned F... max / F min The average value. Therefore, the aforementioned reduction temperature is set to 450°C or below. On the other hand, there is no particular limitation on the lower limit of the reduction temperature; by increasing the reduction temperature, the time required for reduction can be shortened. Therefore, the aforementioned reduction temperature is preferably 300°C or above.
[0067] In the aforementioned reduction, hydrogen can be appropriately used as a reducing agent.
[0068] By allowing the aforementioned reduction to proceed for an appropriate time, the iron oxide powder can be sufficiently reduced. Therefore, the aforementioned reduction is preferably carried out for 10 seconds or more.
[0069] In the aforementioned reduction oxidation process, the oxidation temperature is not particularly limited; by increasing the oxidation temperature, oxidation can be achieved in a shorter time. Therefore, the aforementioned oxidation temperature is preferably 300°C or higher. On the other hand, if the oxidation temperature is too high, sintering of the iron oxide powder will occur. Therefore, from the viewpoint of further improving reaction efficiency, the aforementioned oxidation temperature is preferably 1000°C or lower.
[0070] In the aforementioned oxidation process, water vapor can be appropriately used as the oxidant.
[0071] By performing the aforementioned oxidation for an appropriate period of time, the reduced powder can be sufficiently oxidized. Therefore, the aforementioned oxidation is preferably performed for 10 seconds or more.
[0072] Example Hereinafter, the powder involved in this invention will be described in detail based on embodiments.
[0073] First, powder samples A to W, as shown in Tables 1 and 2, were prepared under the conditions indicated in Tables 1 and 2.
[0074] For the example of using a ball mill for the adhesion method in samples A to W, firstly, Fe2O3 powder, Fe3O4 powder, and an oxide containing at least one of Cr and Si are mixed to prepare a raw material powder. The mixing ratio is set to the same ratio as the Fe2O3 content, Fe3O4 content, and oxide powder content shown in Table 1. Furthermore, the oxides containing at least one of Cr and Si are of the types shown in Table 1. It should be noted that for sample A, no oxide powder is mixed. Next, the aforementioned raw material powder is mixed using a ball mill. During the mixing process, the aforementioned raw material powder and ZrO2 grinding balls (10 mm) for mixing are added to a container made of ZrO2. The ethanol was added at a ratio of 50 ml to 10 g of the aforementioned raw material powder. Then, the mixture was mixed for at least 2 hours using a ball mill (Fritsch pulverisette 7) at the rotation speeds shown in Table 1. For example, sample T was mixed at a rotation speed of 600 rpm for 2 hours.
[0075] Next, for samples other than A and T, the aforementioned mixed powder was heat-treated at 600°C for 2 hours. For samples A and T, no heat treatment was performed.
[0076] Next, the heat-treated powder was exposed to a hydrogen atmosphere at the reduction temperatures shown in Table 1 to reduce the iron oxide to metallic iron. Then, it was exposed to a water vapor atmosphere at the oxidation temperatures shown in Table 1 to oxidize the metallic iron, thus obtaining a sample. The content of iron oxide particles and oxide particles in the obtained sample was equivalent to the content of iron oxide powder and oxides containing at least one of Cr and Si in the aforementioned raw material powder. It should be noted that no reduction oxidation was performed on samples A and T.
[0077] In another example, using vacuum evaporation as the adhesion method, Cr2O3 was coated onto Fe2O3 powder using vacuum evaporation, thereby preparing a sample. In this case, regarding the Fe2O3 content and oxide powder content shown in Table 1, the mass difference before and after vacuum evaporation was taken as the mass of the oxide powder, and the mass was calculated using the mass of the oxide powder and the mass of the Fe2O3 powder before vacuum evaporation. Next, for sample S, heat treatment, reduction, and oxidation were performed in the same manner as in the case using the ball mill described above. The resulting sample contained iron oxide particles and oxide particles at the same levels as the Fe2O3 content and oxide powder content shown in Table 1.
[0078] In the example where nitric acid Cr impregnation is used as the adhesion method, iron oxide powder is impregnated in a Cr(NO3)3 solution of 35% or more, forming a Cr-containing compound on the surface. Alternatively, in the example where nitric acid Mn impregnation followed by nitric acid Cr impregnation is used as the manufacturing method, iron oxide powder is impregnated in a solution containing a total of 35% or more Mn(NO3)2 and Cr(NO3)3, and then impregnated in a Cr(NO3)3 solution of 35% or more, forming a Cr-containing compound on the surface.
[0079] Next, the powder after impregnation is dried at 200°C, decomposed by salt at 400°C, and then heat-treated at 600°C for 2 hours.
[0080] Next, the heat-treated powder was exposed to a hydrogen atmosphere at the reduction temperature shown in Table 2 to reduce the iron oxide to metallic iron. Then, it was exposed to an atmosphere containing water vapor at the oxidation temperature shown in Table 2 to oxidize the metallic iron and obtain a sample.
[0081] The resulting powder contains oxide particles that contain elements of the types shown in Tables 1 and 2 in the form of oxides.
[0082] (Average particle size of oxide particles and F) max / F min (Determination of average value and average contact rate) Regarding the average particle size of oxide particles and F max / F min The average value was calculated using SEM measurements.
[0083] First, the obtained sample was observed by SEM under an accelerating voltage of less than 5 kV and a magnification of more than 100,000 times to obtain images of the sample. The obtained images were read using commercially available image processing software (ImageJ, etc.) to calculate the equivalent circle diameter and Freette diameter of the oxide particles.
[0084] The above processing was performed on arbitrarily selected 10 oxide particles, and the average equivalent circle diameter of the 10 oxide particles was taken as the average particle size. Additionally, for each oxide particle, the maximum value of the Ferrette diameter (maximum Ferrette diameter) F was calculated. max and the minimum value (minimum Freret diameter) F min For each oxide particle, calculate their ratio F. max / F min Then, F max / F min The average value is used as the F of the oxide particles of the aforementioned sample. max / F min The average value.
[0085] In addition, the average contact rate was calculated using STEM and EDS.
[0086] The obtained sample was resin-embedded and processed by focused ion beam (FIB) to cut out a powder cross-section with a thickness of less than 50 nm. STEM images were obtained at a magnification of approximately 640,000 times. Using the obtained mapping images of one or both of Cr and Si, the average contact rate of oxide particles in contact with the surface of iron oxide particles was calculated.
[0087] Specifically, for oxides containing Cr, regions with a Cr / Fe mass concentration ratio of 0.2 or higher are identified as oxide particles. Then, regions of iron oxide particles are identified in the microscopic image, and the ratio of the length of the contact area between the iron oxide particle region and the oxide particle region to the outer perimeter of the iron oxide particle region is calculated as the contact rate. This process is performed on 10 fields of view, and the average of the obtained contact rates is taken as the average contact rate.
[0088] In addition, for oxide particles containing Si, regions with a Si / Fe mass concentration ratio of 0.1 or higher are identified as oxide particles, and the above processing is performed to calculate the average contact rate.
[0089] (evaluate) The performance of each obtained sample as a negative electrode active material was evaluated.
[0090] (Reaction efficiency and the rate of decrease in reaction efficiency) First, the reaction efficiency and the rate of reduction of the reaction efficiency described later were evaluated using the samples involved in each embodiment in powder form. Figure 3The apparatus used in this evaluation is shown. Cell 6 has a capacity of 20 cc and contains the sample 7 (50 mg) involved in each embodiment. A gas inlet and a gas outlet are provided in cell 6 to allow gas flow, and the cell is sealed except for these two parts. A valve is provided in the gas outlet to prevent the ingress of external gas and to maintain the internal pressure at 1 atmosphere. Cell 6 is mounted on a thermobalance (not shown) capable of gas introduction and heating.
[0091] Cell 6 was kept at 400°C and repeatedly subjected to reduction treatment of iron oxide (achieved by introducing hydrogen at 100 ml / min for 60 min) and oxidation treatment of iron (achieved by introducing 2.8 vol% water vapor for 180 min). The introduction of hydrogen and water vapor was carried out while maintaining the interior of cell 6 at 1 atmosphere. As shown in the reaction formula below, through reduction treatment, iron oxide becomes metallic iron, and through oxidation treatment, metallic iron is oxidized to Fe3O4. Furthermore, by repeatedly introducing hydrogen and water vapor, the mass of sample 7 changed.
[0092] 4H₂ + Fe₃O₄ → 3Fe + 4H₂O (reduction treatment) 3Fe + 4H₂O → 4H₂ + Fe₃O₄ (oxidation treatment) Therefore, the mass change ΔM of sample 7 caused by each reduction and oxidation treatment was measured.
[0093] Starting with the mass (M0) of the powder at the point where the initial reduction treatment is completed, one oxidation treatment and one reduction treatment are considered as one cycle. After each cycle of oxidation treatment, the mass (M1) of the first cycle, the mass (M2) of the second cycle, ..., the mass (Mn) of the nth cycle are measured. n At this point, the mass change ΔM in the nth cycle is... n Defined as M n -M0. Furthermore, assuming that the iron oxide contained in the samples involved in each embodiment is completely converted to metallic iron in the initial reduction treatment, and that the metallic iron is completely oxidized in the next oxidation treatment so that all the iron contained is Fe3O4, the theoretical mass change in the first cycle is defined as ΔM. R .
[0094] First, in order to evaluate the reaction efficiency, we evaluate ΔM1 / ΔM. R The evaluation criteria are as follows. A result of 1 to 2 indicates excellent reaction efficiency.
[0095] 1: More than 90% 2: 70% or more but less than 90% 3: 50% or more but less than 70% 4: Less than 50% Next, to evaluate the rate of decrease in reaction efficiency due to repeated use, ΔM was evaluated. 20 / ΔM1. The evaluation criteria are as follows. When the result is 1 to 2, it can be evaluated that the reaction efficiency can be maintained even if the redox reaction is repeated.
[0096] 1: More than 90% 2: 70% or more but less than 90% 3: 50% or more but less than 70% 4: Less than 50% (Fill rate) Furthermore, considering its practical application as a battery material, etc., the filling rate and the rate of reduction in reaction efficiency (described later) were evaluated using molded bodies prepared from the samples involved in each embodiment. 10g of each sample was prepared and placed in a cylindrical compression molding machine, and a constant load of 0.5MPa was applied for 1 minute for compression molding, thereby producing a molded body. The density of the molded body was calculated based on its volume, and the density of the molded body was divided by the density of the iron oxide particles to determine the filling rate. The evaluation criteria for the filling rate are as follows. A result of 1 indicates suitability for use as a battery material and reactant.
[0097] 1: 0.2 or more 2: Less than 0.2 (This represents the rate of reduction in reaction efficiency under real-world conditions.) The aforementioned molded body was kept at 400°C and subjected to repeated reduction treatment of iron oxide (conducted by introducing hydrogen at 100 ml / min for 60 min) and oxidation treatment of iron (conducted by introducing 2.8 vol% water vapor for 180 min). The introduction of hydrogen and water vapor was carried out to maintain the internal pressure of cell 6 at 1 atmosphere. The mass change ΔN caused by the reduction and oxidation treatments was measured.
[0098] Starting with the mass (N0) of the powder at the point where the initial reduction treatment is completed, one oxidation treatment and one reduction treatment are considered as one cycle. After each cycle of oxidation treatment, the mass (N1) of the first cycle, the mass (N2) of the second cycle, ..., the mass (Nn) of the nth cycle are measured. n At this point, the mass change ΔN in the nth cycle is... n Defined as N n-N0. Furthermore, for each embodiment, the mass of the molded body, assuming a fill rate of 1.0, is calculated as the product of the volume of the molded body and the density of the iron oxide particles. Then, using an amount of powder equivalent to this mass, and assuming that all the iron contained in the powder is reduced and oxidized during the initial reduction and oxidation processes, the theoretical mass change in the first cycle is defined as ΔN. C .
[0099] To evaluate the rate of decrease in reaction efficiency caused by repeated use in environments where the cells are intended to be filled, but which are actually used, the efficiency ΔN was evaluated. 20 / ΔN C The evaluation criteria are as follows. A result of 1 to 2 indicates that the reaction efficiency can be maintained even when repeated redox reactions are carried out under actual operating conditions.
[0100] 1: More than 30% 2: 20% or more but less than 30% 3: 10% or more but less than 20% 4: Less than 10% The evaluation results are shown in Tables 3 and 4.
[0101] [Table 1] [Table 2] [Table 3] [Table 4] Industrial availability By using the powder involved in this invention, it is possible to manufacture long-life hydrogen production devices and negative electrode active materials for iron-air batteries. Therefore, this invention is useful for building a future hydrogen energy society.
[0102] Explanation of reference numerals in the attached figures 1. Negative electrode active material 2. Air electrode 3. Solid electrolytes 4 Negative electrode 5. Metal-air batteries 6 battery cells 7. Sample.
Claims
1. A powder comprising: Iron oxide particles; and oxide particles, The oxide particles contain at least one of Cr and Si in the form of oxides. The average particle size of the oxide particles is between 0.5 nm and 100 nm. The maximum Freette diameter F of the oxide particles max With the minimum Fret diameter F min The ratio of F max / F min The average value is above 2.
0. The oxide particles are in contact with the iron oxide particles at an average contact rate of 20% to 80% relative to the iron oxide particles.
2. A negative electrode active material for a metal-air battery, which uses the powder described in claim 1.
3. A reactant for a hydrogen production apparatus, which uses the powder described in claim 1.
4. A method for manufacturing the powder according to claim 1, comprising: An adhesion process that attaches a compound containing at least one of Cr and Si to iron oxide powder; A heat treatment process that involves heat treatment of the adhered powder; and A reduction-oxidation process is performed on the heat-treated powder at a reduction temperature below 450°C, followed by oxidation of the reduced powder.
5. The method for manufacturing the powder as described in claim 4, wherein, The attachment process is to... Iron oxide powder: 80% or more, and A mixing process involving powders containing oxides of at least one of Cr and Si: 3% or more of the powder is mixed.
Citation Information
Patent Citations
Negative electrode for air battery, and solid electrolyte air battery using the same
JP2015216109A
Powder containing iron oxide particles and negative electrode material for metal air battery
JP2022015292A